Symptoms in long-term breast cancer survivors: A cross-sectional study in primary care. (December 2020) - Maass, S.W.M.C.; Boerman, L.M.; Brandenbarg, D.; Verhaak, P.F.M.; Maduro, J.H.; de Bock, G.H.; Berendsen, A.J.
Abstract: Purpose: Various long-term symptoms can manifest after breast cancer treatment, but we wanted to clarify whether these are more frequent among long-term breast cancer survivors than matched controls and if they are associated with certain diagnoses. Methods: This was a cross-sectional, population-based study of 350 breast cancer survivors treated with chemo- and/or radiotherapy ≥5 years (median 10) after diagnosis and 350 women without cancer matched by age and primary care physician. All women completed a questionnaire enquiring about symptoms, underwent echocardiography to assess the left ventricle ejection fraction, and completed the Hospital Anxiety and Depression Scale. Cardiovascular diseases were diagnosed from primary care records. In a multivariable logistic regression analysis, symptoms were adjusted for the long-term effects and compared between cohorts and within the survivor group. Results: Concentration difficulties, forgetfulness, dizziness, and nocturia were more frequent among breast cancer survivors compared with controls, but differences could not be explained by cardiac dysfunction, cardiovascular diseases, depression, or anxiety. Intermittent claudication and appetite loss were more frequent among breast cancer survivors than controls and associated with cardiac dysfunction, depression, and anxiety. Breast cancer survivors treated with chemotherapy with/without radiotherapy were at significantly higher odds of forgetfulness and nocturia, but significantly lower odds of dizziness, compared with breast cancer survivors treated with radiotherapy alone. Conclusions: Intermittent claudication and appetite loss are common among breast cancer survivors and are associated with cardiac dysfunction and mood disorders. Other symptoms varied by whether the patient underwent chemotherapy with/without radiotherapy (forgetfulness and nocturia) radiotherapy alone (dizziness). Highlights: Even 10 years after diagnosis, breast cancer survivors experience various long-term symptoms. Some symptoms are more common among breast cancer survivors than among controls without cancer. Not all symptoms are associated with known cardiovascular or psychological diagnoses. A symptom-specific approach may be appropriate. This study does not evaluate a causal relation.